Pengaruh Pemberian Ekstrak Etanol Kelopak Bunga Rosella (Hibiscus sabdariffa, L) Terhadap Kadar LDL Pada Mencit Putih Betina - Surya Dharma; Erdinal Erdinal; Zet Rizal (STIFARM Padang, 2010)
Research on the effect of roselle calyx ethanol extract (Hibiscus sabdariffa Linn) on the levels of LDL female white mice have been done. The extract was administered orally with a variety doses 500, 700 and 1000 mg /kg bw once daily for 7, 14 and 21 days. as a negative control group using white female mice were given standard diet, while the positive control were given atherogenic cocktail as induction . The results showed that the ethanol extract of roselle calyx apparently have a significant effect on levels of LDL blood cholesterol of female white mice. dose of 28 mg/20 g bw showed reduced blood levels of LDL cholesterol better than a dose of 14 mg/20g bw and 19.6/20g bw. Based on further test duncan, reduced levels of LDL cholesterol on day 21 showed excellent results compared to most day 7th and 14th.